Using technology to enhance medication regimen education after solid organ transplantation. (1st December 2018) - Tsapepas, Demetra S.; Salerno, David; Jandovitz, Nicholas; Hammad, Sara; Jordan, Patrick; Mohan, Sumit; Hardy, Mark; Kotchoubey, Helen; Vawdrey, David; Fleischut, Peter M.
Abstract: Purpose: The design and implementation of a tool that combines clinical teaching with cutting-edge, simplified technology for providing medication education to solid organ transplant (SOT) recipients are described. Methods: In a retrospective study of adults who received kidney transplants from February 2015 through May 2017, patients were educated about their medications using a tablet computer application, Medication Regimen Education (MRxEd), that presented concise videos describing the name, indication, dose, adverse effects, and associated interactions of all medications received, as well as special considerations applicable to each agent. Assessment questions were used to reinforce key concepts and identify knowledge gaps. Results: The digital educational intervention was provided to 282 kidney transplant recipients. Patients were predominantly white (48%) and/or male (63%), with a median age of 51 years (interquartile range, 37–61 years). Patients came from a variety of education backgrounds. Most patients (81%) were educated on dual maintenance immunosuppression (with tacrolimus and mycophenolate) and 3 infection prophylaxis agents (nystatin, sulfamethoxazole–trimethoprim, and valganciclovir). Most patients (90%) correctly answered questions related to medication indications, dosing, and special rules, but many (61%) had difficulty correctly answering questions about adverse effects. Conclusion: An innovative approach for interactive and engaging medication teaching with the MRxEd application enhanced the education process for SOT recipients.